Tumor-Induced CD8+ T-Cell Dysfunction in Lung Cancer Patients - Heriberto Prado-Garcia; Susana Romero-Garcia; Dolores Aguilar-Cazares; Manuel Meneses-Flores; Jose Sullivan Lopez-Gonzalez (Clinical and Developmental Immunology)
Lung cancer is the leading cause of cancer deaths worldwide and one of the most common types of cancers. The limited success of chemotherapy and radiotherapy regimes have highlighted the need to develop new therapies like antitumor immunotherapy. CD8+ T-cells represent a major arm of the cell-mediated anti-tumor response and a promising target for developing T-cell-based immunotherapies against lung cancer. Lung tumors, however, have been considered to possess poor immunogenicity; even so, lung tumor-specific CD8+ T-cell clones can be established that possess cytotoxicity against autologous tumor cells. This paper will focus on the alterations induced in CD8+ T-cells by lung cancer. Although memory CD8+ T-cells infiltrate lung tumors, in both tumor-infiltrating lymphocytes (TILs) and malignant pleural effusions, these cells are dysfunctional and the effector subset is reduced. We propose that chronic presence of lung tumors induces dysfunctions in CD8+ T-cells and sensitizes them to activation-induced cell death, which may be associated with the poor clinical responses observed in immunotherapeutic trials. Getting a deeper knowledge of the evasion mechanisms lung cancer induce in CD8+ T-cells should lead to further understanding of lung cancer biology, overcome tumor evasion mechanisms, and design improved immunotherapeutic treatments for lung cancer.